Cordycepin Suppresses Excitatory Synaptic Transmission in Rat Hippocampal Slices Via a Presynaptic Mechanism - Yao, Li‐Hua (CNS Neurosci Ther, 2013)
AIMS: Cordycepin plays an important role in modulating the function of central nervous system (CNS). However, the modulating mechanism is poorly understood. Excitatory synaptic transmission, the essential process in brain physiology and pathology, is critical in the signal integration activities of the CNS. To further understand the effects of cordycepin on CNS, we investigated the effects of cordycepin on excitatory synaptic transmission in the CA1 region of rat hippocampal slices. METHODS: The effects of cordycepin on excitatory synaptic transmission were investigated by using in vitro field potential electrophysiology and whole‐cell patch clamp techniques. RESULTS: Cordycepin significantly decreased the amplitudes of field excitatory postsynaptic potentials (fEPSPs) elicited in the CA1 by stimulation of the Schaffer‐commissural fibers. And the reduction in fEPSPs amplitude was associated with an increase in the paired‐pulse facilitation. Cordycepin also suppressed α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazole‐propionic acid (AMPA) and N‐methyl‐d‐aspartic acid (NMDA) receptor‐mediated responses but did not directly affect AMPA receptors and NMDA receptors. Furthermore, quantal analysis revealed that cordycepin decreased the frequency but not amplitude of miniature spontaneous excitatory postsynaptic currents. CONCLUSIONS: These results demonstrate that cordycepin suppresses excitatory synaptic transmission by decreasing the excitatory neurotransmitter release presynaptically, which provides an evidence for the novel potential mechanism of cordycepin in modulating the function of CNS.